PERAN BADAN PERMUSYAWARATAN DESA (BPD) DALAM PEMBANGUNAN DESA - Amin, Aidil; Roza, Darmini (UNES Journal of Swara Justisia, 2017)
This article is the result of research that discusses the role of BAMUS Nagari in Lubuak Gadang Sangir Subdistrict, South Solok Regency of West Sumatera Province with the role of BPD in Lubuk Nagodang Village, Siulak Subdistrict Kerinci Regency, Jambi Province. This study uses primary data as the main data obtained from interviews and secondary data as support obtained from literature studies. Based on the results of the research, BAMUS Nagari Lubuak Gadang plays an important role in the development of the village, because BAMUS Nagari Lubuak Gadang is very active in collecting the aspirations of the people, establishing the Nagari Regulations well and carrying out supervision on development and development results. Compared with the BPD Lubuk Nagodang is less active in collecting aspirations from the community, the role of BPD in establishing the Village Regulation Lubuk Nagodang also not yet running well and BPD Lubuk Nagodang only oversee the development process without monitoring the results of development.